The Twofold Approach to Children’s Freedom of Movement Rights Under European Law: Can ‘Children’s Equilibrium’ Guide the Interpretation of the Post-Brexit Rights of UK Children Residing in the EU? - Teodora Mariova Petrova (Croatian Yearbook of European Law and Policy, 2018)
The United Kingdom’s decision to leave the EU is causing a strong political, legal and, last but not least, social turmoil. Arguably, the impact is even greater for children who are growing up as part of the Union, and belong to families of mixed nationalities, and/or have cross-border relations to different states and educational systems. The interpretation of the post-Brexit EU law rights of children with British nationality should ﬁrst examine the pre-Brexit children’s rights under the European freedom of movement law to assess the exact scope of the change that the removal of European citizenship will entail. An overview of the case law of the European Court of Justice (“ECJ”) on the freedom of movement rights demonstrates an evolution in the understanding of the rights of children under EU law, a development which observes more and more children’s speciﬁc needs, as embodied in children’s fundamental rights provisions. This development came about in a sporadic fashion, shifting between treating children’s rights as ancillary add-ons to their parents’ EU law market rights and acknowledging children’s individual rights. Eventually, the ECJ attempted to reinforce the latter approach by examining children’s Union citizenship and rights under EU law by referencing children’s fundamental rights, enshrined in Article 24 of the Charter of Fundamental Rights of the European Union, for the sake of maintaining “children’s equilibrium”. The referring to the so-called ‘“children’s equilibrium”’ would suggest that a respective child-related approach was adopted in the interpretation of European law via which the stated equilibrium could be achieved. Yet, apart from the inclusion of Article 24 in the legal discussion, the development of a comprehensive child-related approach with a view to the securing of children’s equilibrium requires further judicial engagement in two main directions. Namely, the need for more guidance remains, especially along the lines of elaborating the EU’s uniform children’s rights obligations and making sure that children are seen as individual rights holders. On the basis of these existing criteria, for the purpose of this paper a child-related approach is to indicate the consideration and integration of children’s rights in the legal reasoning, by regarding children as independent rights-bearing individuals. The paper will argue that the upcoming legal uncertainties could be levelled down if the goal of maintaining children’s equilibrium through the child-related approach was applied in the interpretation of the EU law-related rights of children with British nationality. Further, since the proposed approach could also be based on the Convention on the Rights of the Child, it could also serve as a bridge for the application of the “children’s equilibrium” approach in the UK with a view to a time when the Charter is not to be applicable any longer.